Brain dopamine and serotonin transporter binding are associated with visual attention bias for food in lean men. Issue 8 (17th March 2016) - Koopman, K. E.; Roefs, A.; Elbers, D. C. E.; Fliers, E.; Booij, J.; Serlie, M. J.; la Fleur, S. E.
Abstract : Background: In rodents, the striatal dopamine (DA) system and the (hypo)thalamic serotonin (5-HT) system are involved in the regulation of feeding behavior . In lean humans, little is known about the relationship between these brain neurotransmitter systems and feeding. We studied the relationship between striatal DA transporters (DAT) and diencephalic 5-HT transporters (SERT), behavioral tasks and questionnaires, and food intake. Method: We measured striatal DAT and diencephalic SERT binding with [ 123 I]FP-CIT SPECT in 36 lean male subjects. Visual attention bias for food (detection speed and distraction time) and degree of impulsivity were measured using response-latency-based computer tasks. Craving and emotional eating were assessed with questionnaires and ratings of hunger by means of VAS scores. Food intake was assessed through a self-reported online diet journal. Results: Striatal DAT and diencephalic SERT binding negatively correlated with food detection speed ( p = 0.008, r = −0.50 and p = 0.002, r = −0.57, respectively), but not with food distraction time, ratings of hunger, craving or impulsivity. Striatal DAT and diencephalic SERT binding did not correlate with free choice food intake, whereas food detection speed positively correlated with total caloric intake ( p = 0.001, r = 0.60), protein intake ( p = 0.01, r = 0.44), carbohydrate intake ( p = 0.03, r = 0.39) and fat intake ( p = 0.06, r = 0.35). Conclusions: These results indicate a role for the central 5-HT and DA system in the regulation of visual attention bias for food, which contributes to the motivation to eat, in non-obese, healthy humans. In addition, this study confirms that food detection speed, measured with the latency-based computer task, positively correlates with total food and macronutrient intake.